Monitoring and Crop Watering System Through Smartphones - Mohd, Mohd Sabani; Jamallullail, M.I.; Mostaman, N.A.; Khalid, N M. (Multidisciplinary Applied Research and Innovation, 2020)
The Monitoring and Crop Watering Systems on small and medium scale industries generally are done manually by haul a bucket to watered plants. Therefore, to overcome this weaknesses and disadvantages, in this study, a system was designed to combine the process of crop watering, and monitoring soil condition in one device. Hence, in present project, the system used Arduino to control the water pump by monitoring the soil moisture level. This new designed system is suitable to be used domestically. The hardware system is only monitor by using smartphones and is convenient to carry at anywhere. In this project, the design of the monitoring and crop watering systems has soil moisture sensor to detect the soil moisture condition simultaneously. Furthermore, Arduino Uno is use as the main microcontroller to control all the device. Beside designing, analysis is made to determine its capability to operate in desired condition. The result shows this low cost system also reduces the watering time by 80% when compared to manual watering. Critical aspects of this system are the ergonomic consideration and cost whereas this system was built with low initial value and more practically with only monitoring using smartphone to prevent musculoskeletal disorders (MSD). As the result of this study, an improved monitoring and crop watering system which perform the whole operation of watering system were develop. This is a Mobile Integrated and smart irrigation system using IOT based on application controlled monitoring system.